Aspectos morfológicos e morfométricos de oócitos humanos pré e pós-vitrificação em procedimentos de fertilização in vitro - Maria das Gracas Rocha de Santana Camargos (2013)
The aim of this study was to correlate oocyte morphological and morphometric changes before and after vitrification, to evaluate if the morphometric characteristics of oocytes pre-vitrification are related to the survival of these cells to cryopreservation and to verify whether the morphometric characteristics after thawing of oocytes are related to the occurrence of fertilization after ICSI. PATIENTS AND METHODS: The volunteers involved in this study were patients admitted to the Professor Aroldo Fernando Camargos Laboratory of Human Reproduction at Hospital das Clínicas UFMG who underwent ovulation induction for assisted reproduction. The investigation included 28 patients and 71 vitrified oocytes. Oocytes were identified in the culture dish using magnifying stereomicroscope. The oocytes were left in a CO2 incubator for at least 1 hour, photographed for morphological and morphometric evaluations and then vitrified individually following the protocol of Irvine Scientific. Measurements and ratings of oocytes, zygotes and embryos in the second and third days of culture were performed using Cronus Software TM. The following morphological features of oocytes were assessed: cytoplasmic granules, polar body fragmentation, cytoplasmic inclusions and vacuoles. RESULTS: There was no correlation between morphological and morphometric characteristics of the 71 evaluated oocytes before vitrification. The oocyte diameters and the measurements of perivitelline space (PS), zona pellucida (ZP) and polar body (PB) were similar in oocytes classified as optimal morphology (N=40) and those with altered morphology (N=31). Out of 49 thawed oocytes, 22 had degenerated and 27 were preserved, including 20 with optimal morphology and 7 with suboptimal morphology. While the oocyte diameter, the PS and ZP measurements were similar in thawed oocytes with optimal and suboptimal morphology, the latter group showed a significant reduction of the measure of PB (11.8 [10.5 to 13.0] m versus 13.2 [12.2 to 15.3] m P=0.013). The morphometric parameters of fresh oocytes were not predictive of oocyte survival to vitrification and thawing. Of the 27 oocytes that survived the cryopreservation process and underwent ICSI, 13 were fertilized. The diameters of oocytes after thawing were lower in the fertilized oocytes (76.0 [73.0 to 78.3] m) compared to those not fertilized (80.5 [73.9 to 82.6] m, P=0.043). The latter group also had shorter PS. CONCLUSION: The morphologic and morphometric characteristics of fresh oocytes are not related to their resistance to vitrification. However, after thawing, fertilization failure is associated with larger oocyte diameter and shorter PS.